Effect of the coverage of rapid tests for syphilis in primary care on the syphilis in pregnancy in Brazil - Angelo Giuseppe Roncalli; Tatyana Maria Silva de Souza Rosendo; Marquiony Marques dos Santos; Ana Karla Bezerra Lopes; Kenio Costa de Lima (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE: To analyze the effect of rapid tests coverage in Primary Care on syphilis detection rate in pregnant women in Brazil, in municipalities with more than 100,000 inhabitants. METHODS: The dependent variable was the syphilis detection rate in pregnant women between 2012 and 2018. As the main independent variables, the methods for measuring the coverage of rapid tests for syphilis in Primary Care were used and, as adjustment variables, some indicators of health services and socioeconomic. We opted for a linear regression model for panel data (panel data analysis), considering the municipality as the unit of analysis and the year as the time variable. RESULTS: From the results of the final model, we can infer that, for a given municipality, as the rate of rapid tests increases by one point for every thousand live births, the detection rate of syphilis in pregnant women increases by an average of 0.02 cases per thousand live births (p < 0.001). This value is adjusted for Family Health coverage, proportion of health facilities per inhabitant, per capita expenditure on health and the Human Development Index. CONCLUSIONS: There was a substantial improvement in the amount of rapid tests available, as well as a significant increase in the number of tests performed in pregnant women, which predicts an increase in syphilis rates in pregnant women. However, a worrying hypothesis is that the number of tests performed on pregnant women during the analyzed period may have been insufficient to detect the progress of the epidemic in this population.